ERPs predict symptomatic distress and recovery in sub-acute mild traumatic brain injury. (September 2019) - Cavanagh, James F.; Wilson, J. Kevin; Rieger, Rebecca E.; Gill, Darbi; Broadway, James M.; Story Remer, Jacqueline Hope; Fratzke, Violet; Mayer, Andrew R.; Quinn, Davin K.
Abstract: Mild traumatic brain injury (mTBI) can affect high-level executive functioning long after somatic symptoms resolve. We tested if simple EEG responses within an oddball paradigm could capture variance relevant to this clinical problem. The P3a and P3b components reflect bottom-up and top-down processes driving engagement with exogenous stimuli. Since these features are related to primitive decision abilities, abnormal amplitudes following mTBI may account for problems in the ability to exert executive control. Sub-acute (<2 weeks) mTBI participants (N = 38) and healthy controls (N = 24) were assessed at an initial session as well as a two-month follow-up (sessions 1 and 2). We contrasted the initial assessment to a comparison group of participants with chronic symptomatology following brain injury (N = 23). There were no group differences in P3a or P3b amplitudes. Yet in the sub-acute mTBI group, higher symptomatology on the Frontal Systems Behavior scale (FrSBe), a questionnaire validated as measuring symptomatic distress related to frontal lobe injury, correlated with lower P3a in session 1. This relationship was replicated in session 2. These findings were distinct from chronic TBI participants, who instead expressed a relationship between increased FrSBe symptoms and a lower P3b component. In the sub-acute group, P3b amplitudes in the first session correlated with the degree of symptom change between sessions 1 and 2, above and beyond demographic predictors. Controls did not show any relationship between FrSBe symptoms and P3a or P3b. These findings identify symptom-specific alterations in neural systems that vary along the time course of post-concussive symptomatology. Highlights: Executive symptoms in chronic TBI participants related to a smaller P3b. Conversely, executive symptoms in sub-acute TBI participants related to a smaller P3a. This relationship in sub-acute TBI participants was replicated 2 months later. P3b predicted independent variance in sub-acute symptom recovery over this time period.